2014
DOI: 10.1007/s12257-013-0454-6
|View full text |Cite
|
Sign up to set email alerts
|

Minor differences in sand physicochemistry lead to major differences in bacterial community structure and function after exposure to synthetic acid mine drainage

Abstract: The formation of environmentally toxic acidic waste from mining activities is a world-wide problem. Neutralization of this waste can be accomplished by physicochemical and/or biological means. In this short-term study, synthetic acid mine drainage was added to sandfilled mesocosms containing silica-dominated (quartz) sand. Glucose was added as a carbon source for microbial iron and/or sulphate reduction. Replicates contained two separate batches of sand obtained from the same quarry site. The investigations us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Nonetheless, the silica particles or grit in the mixed liquor can interact with the microbes by acting as a bacteria carrier or changing the structure of the sludge flocs, eventually changing the bacterial community structure of the mixed liquor. This assumption could be supported by a previous finding that subtle differences in the properties of sand led to considerable differences in the bacterial community [7].…”
Section: Influence Of the Grit On The Bacterial Community Structurementioning
confidence: 53%
See 1 more Smart Citation
“…Nonetheless, the silica particles or grit in the mixed liquor can interact with the microbes by acting as a bacteria carrier or changing the structure of the sludge flocs, eventually changing the bacterial community structure of the mixed liquor. This assumption could be supported by a previous finding that subtle differences in the properties of sand led to considerable differences in the bacterial community [7].…”
Section: Influence Of the Grit On The Bacterial Community Structurementioning
confidence: 53%
“…Although the grit does not contribute to biological reactions directly, these particles can be potentially involved in the formation of sludge flocs; e.g., small grit can be entrapped by sludge flocs. Because of the high specific area, the grit could be considered as a bacterial media that can affect the growth of the bacteria and thus change the structure of the bacterial community [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of water regime history might be balanced by several salts, such as Ca + , K + , Na + as well as S content, which all presented substantial variations between the riverbed and gravel plain soils, although not significantly different (p > 0.05). As an extreme example, it has indeed been shown that even minor differences in sand crystal composition can lead to completely distinct microbial community structures 43 .…”
Section: Resultsmentioning
confidence: 99%
“…Our data do indicate that fine grains, silts and clays [VFS, SC, ST, CY] are positively correlated with metals [Fe/Mn/Al], minerals [Ca/Mg] and some nutrients (C, P, NO − 3 -N, NH + 4 -N) (Figure 2 ). This suggests that the relationship between bacterial diversity, soil structure and nutrient contents needs further investigation in dune soils as subtle differences in sand mineralogy and micronutrient contents has been shown to significantly impact edaphic community structuring (Welz et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%